2009
DOI: 10.1002/acr.20008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging grading system for active and chronic spondylarthritis changes in the sacroiliac joint

Abstract: Objective. To develop a new grading method to quantify activity and chronic spondylarthritis (SpA) changes in the sacroiliac (SI) joints identified by magnetic resonance imaging (MRI), taking into account the complex joint anatomy, and to compare the findings with radiographic changes. Methods. A total of 37 patients (15 men, 22 women) fulfilling the European Spondylarthropathy Study Group criteria for SpA were examined by MRI of the SI joint using a semicoronal T1-weighted and T1-weighted fat-saturated (T1FS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
74
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 18 publications
3
74
2
4
Order By: Relevance
“…All patients contacted the clinic because of a knee joint effusion, none received biological treatment, but all received standard disease-modifying antirheumatic drugs (DMARD). [16,17]. The methods have proven a reliable inter-and intra-observer agreement with kappa values in the range of 0.62-1.0.…”
Section: Collection Of Samplesmentioning
confidence: 86%
See 1 more Smart Citation
“…All patients contacted the clinic because of a knee joint effusion, none received biological treatment, but all received standard disease-modifying antirheumatic drugs (DMARD). [16,17]. The methods have proven a reliable inter-and intra-observer agreement with kappa values in the range of 0.62-1.0.…”
Section: Collection Of Samplesmentioning
confidence: 86%
“…The clinical scorings comprise Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), physicians' global score on a 100-mm visual analog scale (VAS), and C-reactive protein (CRP). The radiological examinations included radiography and MRI of the SIJ and spine [16,17]. Plasma from age-and gender-matched healthy volunteers (HV) (n = 35) served as controls (Table 1).…”
Section: Collection Of Samplesmentioning
confidence: 99%
“…Erosions are identified as high or intermediate signal defects in the hypointense cortical bone on these sequences. One study used both T1W and T1FS to identify erosions in the SIJ and showed good reliability for an erosion score based on the extent of involvement of the joint surface, although this study did not directly compare these two sequences as regards reliability of detection or diagnostic utility [32]. A recent report compared T1W FS with spin-echo, threedimensional-fast low angle shot (3D-FLASH), and threedimensional-double excitation in the steady-state (3D-DESS) sequences in a retrospective analysis of scans from 30 patients with suspected sacroiliitis and 9 healthy controls [33].…”
Section: Mri In Axial Spa-major Component Of New Classification Criteriamentioning
confidence: 99%
“…Erosion Bone erosion has been defined as full-thickness loss of the dark appearance of either iliac or sacral cortical bone of the SIJ with loss of the adjacent marrow signal on T1SE images [32].…”
Section: Mri In Axial Spa-major Component Of New Classification Criteriamentioning
confidence: 99%
“…However, these have generally focused on global assessment either of the joint or of joint quadrants as a whole 7,8 , not on separate scoring of individual slices. The new SSS method 3 potentially provides a higher sensitivity to change and additionally allows a detailed assessment of the temporal and spatial relation between the individual pathologies.…”
mentioning
confidence: 99%